2010
DOI: 10.4238/vol9-1gmr710
|View full text |Cite
|
Sign up to set email alerts
|

Additive genetic relationship of longevity with fertility and production traits in Nellore cattle based on bivariate models

Abstract: ABSTRACT. Survival or longevity is an economically important trait in beef cattle. The main inconvenience for its inclusion in selection criteria is delayed recording of phenotypic data and the high computational demand for including survival in proportional hazard models. Thus, identification of a longevity-correlated trait that could be recorded early in life would be very useful for selection purposes. We estimated the genetic relationship of survival with productive and reproductive traits in Nellore cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
4
16
1
2
Order By: Relevance
“…The posterior mean heritability of SURV, measured as the liability to reach the following parity was 0.05, substantially lower than the results presented by Gonzá lez-Recio and Alenda (2007) and Van Melis et al (2010) using the same statistical approach as Holstein and Nellore, respectively. Moreover, the figure is within the range of results reported by Forabosco et al (2006) and Zavadilova et al (2009) in Chianina and Fleckvieh or Simmental, using linear models and survival analysis.…”
Section: Survcontrasting
confidence: 66%
See 1 more Smart Citation
“…The posterior mean heritability of SURV, measured as the liability to reach the following parity was 0.05, substantially lower than the results presented by Gonzá lez-Recio and Alenda (2007) and Van Melis et al (2010) using the same statistical approach as Holstein and Nellore, respectively. Moreover, the figure is within the range of results reported by Forabosco et al (2006) and Zavadilova et al (2009) in Chianina and Fleckvieh or Simmental, using linear models and survival analysis.…”
Section: Survcontrasting
confidence: 66%
“…The results indicate a positive correlation of survival with W120, W210, CCW and FAT and negative correlation with CON. A positive genetic correlation with weight has previously been suggested by several authors (Rogers et al, 2004;Tarres et al, 2004;Zavadilova et al, 2009;Van Melis et al, 2010). However, there was almost no correlation with BW; this was probably caused by the positive correlation between dam and calf BW and by the association of these traits with calving difficulty, as noted previously.…”
Section: Genetic Correlationssupporting
confidence: 50%
“…The heritabilities estimated in the present study are within the range reported in the literature for Nellore cattle, with estimates of 0.22-0.55 for WW, 0.17-0.20 for AFC, and 0.25-0.30 for WG (Pereira et al, 2001(Pereira et al, , 2002Van Melis et al, 2010;Boligon et al, 2010Boligon et al, , 2011. Similarly, maternal heritability (0.07 ± 0.01) for WW was similar to estimates obtained in other Nellore herds (Pereira et al, 2001;Boligon et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Neves et al (2012) estimated 0.17 for heritability using the same definition of NC53. Van Melis et al (2010) presented estimates of heritability ranging from 0.17 to 0.20 in multivariate analysis for survival (number of calvings until cow death), using a sequential threshold model. Generally, most of the studies related to the evaluation of traits that measure longevity or length of productive life in cows, do it by adopting STAY in the following definition: probability of a cow to remain in herd until a specific age, when the opportunity to reach that age is given (Hudson and Van Vleck, 1981).…”
Section: Resultsmentioning
confidence: 99%